Role of Ozone Therapy in Minimal Intervention Dentistry and Endodontics - A Review - A, Shilpa Reddy (International Society of Preventive and Community Dentistry, 2013)
Ozone has been successfully used in medical field since many years owing to its oxidizing property making it an excellent antimicrobial agent. Moreover its potent anti-inflammatory property along with favorable cellular and humoral immune response made ozone an effective therapeutic agent. Also its ability to arrest and reverse carious lesions in a predictable way opened up a new chapter in minimal intervention dentistry. Furthermore its efficacy in curbing resistant poly microbial root canal flora appears very promising. This article is based on information through valid textbooks, peer reviews, journals and medline/pubmed search. How to cite this article: Reddy S A, Reddy N, Dinapadu S, Reddy M, Pasari S. Role of Ozone Therapy in Minimal Intervention Dentistry and Endodontics - A Review. J Int Oral Health 2013; 5(3):102-108.